Quantum-coherently assisted deep-UV localization of photonic states in active stopped-light plasmonic heterostructures - K. L. Tsakmakidis; Jha, P.K.; Wang, Y.; Zhang, X. (Conference on Lasers and Electro-Optics Europe - Technical Digest, 2015)
We introduce a new method to localize lightwaves. We show how the interaction of a gain medium with a planar deep-UV plasmonic heterostructure, at its zero-vg point, strongly localizes light. A quantum-coherent drive provides a means to control the localization and dramatically improve the dynamics. © 2015 OSA.